Functional and radiological outcome of minimally invasive percutaneous plate osteosynthesis in distal third tibia fracture - Dhakal, Rabi Mohan; Chaudhary, Sunil Kumar; Bista, Krishna Bahadur; Parajuli, Anjali; Panta, Prayash (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Distal one-third tibia fractures are among the most frequent lower limb injuries, often resulting from high-velocity trauma. The morbidity associated with these fractures arises from articular involvement, soft tissue damage, and compromised vascularity. Treatment outcomes largely depend on fracture pattern, bone quality, and associated injuries. This study aimed to evaluate the functional and radiological outcomes of minimally invasive percutaneous plate osteosynthesis (MIPPO) in distal third tibia fractures. Methods: This prospective study was conducted at Gandaki Medical College, Pokhara, over 12 months, enrolling 45 patients aged 18–60 years with closed, displaced, extra-articular distal tibia fractures. Following informed consent, all patients underwent MIPPO using a distal tibia locking plate (DTLP) and were followed for six months. Functional outcomes were assessed using the American Orthopedic Foot and Ankle Society (AOFAS) score at six months, and radiological union was recorded in weeks. Results: The mean patient age was 37 years, with the highest proportion in the 20–30-year age group (n=16, 35.5%). Radiological union occurred at 12 weeks in 30 patients (66.6%) and at 24 weeks in 15 patients (33.4%). At six months, 26 patients (57.7%) scored 90–95 on the AOFAS scale, 10 (22.2%) scored 75–85, and 9 (20%) scored 50–65. Overall outcomes were excellent in 23 (53.1%), good in 13 (28.9%), fair in 4 (8.9%), and poor in 5 (11.1%). Postoperative complications were minimal, limited to superficial infections in 3 patients (6.7%). Conclusions: MIPPO provides biological advantages, minimizes complications, and significantly improves functional outcomes in distal tibia fractures.